Graphene–Organic Two-Dimensional Charge-Transfer Complexes: Intermolecular Electronic Transitions and Broadband Near-Infrared Photoresponse - Yuzheng Guo (The Journal of Physical Chemistry C, 2018)
Charge-transfer (CT) complexes with unique intermolecular electronic transitions have attracted broad interest and hold great potential in optoelectronic applications. Here, we report a new family of two-dimensional graphene-organic molecule CT complexes. Density functional theory (DFT) calculation has revealed low-energy CT bands in the near-infrared (NIR) region up to 2000 nm for graphene-TCNQ (tetracyanoquinodimethane), graphene-F4TCNQ (2,3,5,6-Tetrafluoro-tetracyanoquinodimethane) and graphene-TCOQ (tetrachloro-o-benzoquinone) complexes. Raman and electrical measurements have confirmed a partial charge transfer between graphene and the molecules at the ground state. CT excitations have been calculated by DFT and verified by optoelectronic measurements. The graphene–organic CT complexes have shown a broadband photoresponse from the visible to NIR range, attributed to the intermolecular electronic transitions. Further, the photoresponsivity (up to 103 A/W) suggests a high photoelectrical gain arising from the photogating effect at the graphene/molecule interface. At last, the photoresponse property of the graphene–organic CT complexes can be tuned by electrical gating of graphene.